The outburst of dammed lake Maashey (North-Chuya ridge, Central Altai) - V. A. Rasputina; G. V. Pryakhina; D. A. Ganyushkin; D. V. Bantcev; S. A. Griga; S. S. Svirepov (Лëд и снег, 2024)
The dammed lakes are widespread in mountainous areas and usually occur when river flow is blocked by landslides, rock glaciers, etc. Among such lakes, the most dangerous are those located in the periglacial zone and blocked by rock glaciers. Continued deglaciation of mountainous areas under changing climate conditions contributes to accumulation of large volumes of melt water in lakes, which may increase pressure on the dam, cause its failure and subsequent outburst flood. In this article we describe the development of such a lake before its outburst and the process of its outburst. The object of study was Maashei Lake (North Chuya Ridge, Central Altai) located in the zone of mountain glaciation and dammed by a rock glacier, where the lake outburst occurred in July 2012. The lake area before the outburst was 259 × 103 m2 and water volume 1.21 × 106 m3. As a result of the outburst, the lake was completely drained. We analyzed the published works on Lake Maashei, materials of our own field studies in the lake basin combined with remote sensing data. We hypothesized that the mechanism of the outburst occurred in 2012 was caused by the water erosion of the filtration channel in the dam body. The mechanism of this outburst was numerically simulated using the method presented in this article. The modeling allowed to reproduce the outburst flood hydrograph, to estimate such characteristics as maximum water discharge, volume of the outburst flood, water flow velocities and the size of the formed breach. Estimated maximum discharge was 694 m3s−1, flow velocities varied from 0.2 to 5-7 m s−1, and the outburst flood period was about 5.5 hours. The breach was formed to the full height of the dam (10 m). Its calculated morphometric characteristics were as follows: average width 47.5 m (measured 41.5m), скоss-section area 476 m2 (measured 415 m2). The discrepancy between the modeled and measured values was about 15 %.